Working with the Presence of a Border: An Artist’s Perspective - Quinn, Dylan (Irish Journal of Arts Management and Cultural Policy, 2019)
Dylan Quinn provides an artist’s perspective of working across the border region in the island of Ireland through discussion of the Here & Now project by Dylan Quinn Dance Theatre. Quinn describes the unique aspects of relationship-building and community engagement in a cross-border, crosscommunity context and calls for greater recognition of the voice of the artist in developing long term policy change for the arts and cultural sector.